PENGARUH CONTAINER SHORTAGE BERDAMPAK PADA TRADE BALANCE JAWA TIMUR DAN PEREKONOMIAN NASIONAL - In'am Widiarma (Sekolah Tinggi Ilmu Ekonomi DR KH EZ Mutaqien, 2022)
East Java's economy has become a benchmark for Indonesia's economic development because it supports the national economy and supports the need for staple goods in eastern Indonesia. In addition, East Java is a logistics hub in the process of sending goods abroad through the TPS Port (Surabaya Container Terminal) and Surabaya Teluk Lamong Terminal so that connectivity is needed to strengthen logistics system services for more effective and efficient exports. The scarcity of containers is a major issue in the process of shipping goods outside, which triggers new problems and increased logistics costs such as an increase in ocean freight, shortage of ship space, congention costs and others. This study uses the analytical method with the PLS (Partial Least Square) program through smartPLS Professional 3.4.0. The results of this analysis are to evaluate the influences involved, in this case the impact of the world of logistics, namely international trade related to the regional and national economy